Reconstructing Islamic Human Development Index in Indonesia - Arsyad, Maulana Kamal; Supriyanto, Achmad Sani; Ekowati, Vivin Maharani (Universitas Airlangga, 2025)
This study aims to examine the construct validity of the Islamic Human Development Index (IHDI) indicators developed by Anto 2011 and Rama & Yusuf 2019 in the context of human development in Indonesia to ensure an appropriate index is obtained. The analysis method used is Principal Component Analysis (PCA) with secondary data from 34 provinces in Indonesia for the year 2024. The results show that two indicators, namely the zakat to GDP ratio and the Gini ratio, were eliminated due to high inter-regional variability. The study identifies four main components that form the IHDI, which are the socio-religious dimension, quality of life, economic welfare, and social mobility, explaining a total variance of 75.72 percent. The novelty of this research lies in the empirical reconstruction of the IHDI using the PCA approach, which produces a measurement structure more representative of the socio-economic conditions in Islamic Indonesia compared to the commonly used IHDI. The findings suggest that the PCA-based IHDI model can serve as a foundation for formulating more representative inter-provincial policies in Indonesia aligned with Islamic ethical values at the provincial level.